1997
DOI: 10.1161/01.hyp.30.4.886
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain-like Factor Quantification in Mammalian Tissues and Plasma

Abstract: The resolution of controversies that concern the detectability of an endogenous ouabain-like factor (OLF) in mammalian tissues and plasma was approached by the application of a standardized method for its extraction and quantification. Two independent assays were used to quantify the OLF: (1) a radioimmunoassay, which used a polyclonal anti-ouabain antiserum, and (2) a radioenzymatic assay based on the inhibition of dog kidney Na+,K+-ATPase. Plasma and tissues were obtained from the Milan hypertensive strain (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
96
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 30 publications
3
96
0
3
Order By: Relevance
“…Elevated EO levels were observed in about 40% of patients with untreated essential hypertension (97) in patients with primary aldosteronism (97) and in those with ACTHinduced hypertension (32,33). Elevated EO levels were also observed in rodents with DOCA-salt hypertension (41,43), ACTH-hypertension (20, 20a, 115), reduced renal mass hypertension (108), and in salt-sensitive Milan strain rats on a high-salt diet (22,23). Indeed, a critical corollary to these reports is the evidence that prolonged administration of ouabain, itself (a Strophanthus steroid), but not digoxin or digitoxin (Digitalis steroids), elevates BP in normal rats and mice (19,60,72,74,75,116).…”
Section: Endogenous Ouabain and Other Endogenous Cardiotonic Steroidsmentioning
confidence: 99%
“…Elevated EO levels were observed in about 40% of patients with untreated essential hypertension (97) in patients with primary aldosteronism (97) and in those with ACTHinduced hypertension (32,33). Elevated EO levels were also observed in rodents with DOCA-salt hypertension (41,43), ACTH-hypertension (20, 20a, 115), reduced renal mass hypertension (108), and in salt-sensitive Milan strain rats on a high-salt diet (22,23). Indeed, a critical corollary to these reports is the evidence that prolonged administration of ouabain, itself (a Strophanthus steroid), but not digoxin or digitoxin (Digitalis steroids), elevates BP in normal rats and mice (19,60,72,74,75,116).…”
Section: Endogenous Ouabain and Other Endogenous Cardiotonic Steroidsmentioning
confidence: 99%
“…Evidence in human hypertension Accumulating evidence has suggested that several sodium pumpinhibitors, similar to cardiotonic steroids, are present in the human body (54). Ouabain-like factor, the most appealing candidate, has been found to increase with high sodium intake and hypervolemia, as well as essential hypertension (55).…”
Section: Ouabain-like Factormentioning
confidence: 99%
“…It has been postulated for some time that endogenous substances [sodium pump inhibitors (SPI)] are stimulated by increased Na intake and increase natriuresis by inhibiting renal tubular Na pumps to prevent renal reabsorption of filtered Na (6,18,30). However, such substances were not purified adequately in early studies, and their assays were nonspecific (17).More recently, SPI assays have improved and become more specific (3,14), and studies in various animal models and in humans have documented an increased elaboration of SPI in response to NaCl loading. This research has focused largely on two SPI: an endogenous ouabain (EO) and a bufadienoide, marinobufagenin (MBG).…”
mentioning
confidence: 99%
“…More recently, SPI assays have improved and become more specific (3,14), and studies in various animal models and in humans have documented an increased elaboration of SPI in response to NaCl loading. This research has focused largely on two SPI: an endogenous ouabain (EO) and a bufadienoide, marinobufagenin (MBG).…”
mentioning
confidence: 99%